Analisis Sistem Informasi Geografis (SIG) untuk Potensi Wisata Pantai di Kota Makasar, Provinsi Sulawesi Selatan - Y Yulius; Taslim Arifin (TATALOKA, 2014)
Makassar city, as a capital of South Sulawesi Province, has potential natural resources with its moderately sloped sandy beach, from north to south. The aims of this research is to identify the potential of oastal tourism in makassar city using GIS spatial analysis. The methods which is used in this study is spatial analysis using GIS. The result hows that Makassar coastal divided into three types, these are: (1) sandy beach, (2) mangrove beach and (3) reclamation beach. Those kind of beaches can be recommended for some tourism activities such as: (1) sandy beach: snorkeling, beach sport, beach volley ball and beach football, beach picnic, swimming, sun bathing, surfing, (2) mangrove beach: field study and (3) reclamation beach: fishing, walking and jogging on beach.Makassar city, as a capital of South Sulawesi Province, has potential natural resources with its moderately sloped sandy beach, from north to south. The aims of this research is to identify the potential of oastal tourism in makassar city using GIS spatial analysis. The methods which is used in this study is spatial analysis using GIS. The result hows that Makassar coastal divided into three types, these are: (1) sandy beach, (2) mangrove beach and (3) reclamation beach. Those kind of beaches can be recommended for some tourism activities such as: (1) sandy beach: snorkeling, beach sport, beach volley ball and beach football, beach picnic, swimming, sun bathing, surfing, (2) mangrove beach: field study and (3) reclamation beach: fishing, walking and jogging on beach.